A 64×64 1200fps CMOS ion-image sensor with suppressed fixed-pattern-noise for accurate high-throughput DNA sequencing - Wang, Fei (2015)
A 64×64 CMOS ion-image sensor is demonstrated towards accurate high-throughput DNA sequencing. Dual-mode (pH/image) sensing is performed with ion-sensitive field-effect transistor (ISFET) fabricated in standard CMOS image sensor (CIS) process. After addressing physical locations of DNA slices by optical contact imaging, local pH for one DNA slice can be mapped to its physical address with accurate correlation. Moreover, pixel-to-pixel ISFET threshold voltage mismatch is reduced by correlated double sampling (CDS) readout. Measurements show a sensitivity of 103.8mV/pH and fixed-pattern-noise (FPN) reduction from 4% to 0.3% with speed of 1200fps. .